The Impact of Symbolic Violence in The Novel Piranesi by Susanna Clarke (2020) - Afif, Fadlurrahman; Alamsyah, Devy Kurnia (Universitas Negeri Padang, 2024)
This study focuses on symbolic violence aspects that are present in the novel entitled Piranesi by Susanna Clarke (2020). The exploration of symbolic violence reveals the systems and mechanisms of how the power dynamics sustained in the environment of the low-populated and labyrinthine world. This study aims to identify the forms and impacts of symbolic violence, and the resistance that the main character commit. In order to analyse the novel, the researcher uses Pierre Bourdieu’s theories of symbolic violence, Alfred Adler’s theories of psychology, and library research to analyse the data. The result of the study shows that the main character experiences manipulation and several forms of symbolic violence, namely Legitimation, Habitus, Doxa, and Domination. Symbolic violence impacts the main character with Inferiority Behaviour, Educational Bias, and Social Imbalance. The main character resist against the symbolic violence with Critical Awareness, Self-Discovery, and Identity Validation. The researcher concludes that symbolic violence is not limited only into a vast area of society, that it can exist in society that only consist of two humans as long as the superiority and inferiority aspects is maintained.